VIARmodes: visualization and iiteraction in mmersive virtual reality for architectural design process - Dias, J.; Coroado, L.; Costa, T.; d'Alpuim, J.; Eloy, S.; Dias, L. (ECAADe 2015: Proceedings of the 33rd International Conference on Education and Research in Computer Aided Architectural Design in Europe, 2015)
The complexity of today´s architecture solutions brings the need to integrate, in the design process, digital tools for creation, visualization, representation and evaluation of design solutions. This paper proposes the adoption of a new Virtual Reality (VR) tool, referred to as VIARmodes, to support the architectural design process with an improved communication across different specialities, towards the facilitation of the project decision process. This tool allows a complete visualization of the design, specifically useful during the detailed design phase, including the architecture design and of other engineering specialities, progressively and interactively adapting the project visualization to the information needed for each discipline. With a set of 3 different visualization modes simulated in real scale within a Virtual Environment (VE), and adopting natural human-computer interaction by using speech, the system allows a team of architect and engineers, to visualize and interact with the proposed design during a collaborative design brief. We carried a usability evaluation study with 12 architects. The study showed that the tool was perceived to be effective and its use efficient during the design process, especially during the detailed design phase.